P149 Piloting and evaluating post-pulmonary rehabilitation (PR) long-term exercise (LTE) for COPD patients. (2nd December 2011) - Roberts, S E; Kettle, G; Rogers, S; Segal, A; Purcell, S; Fabris, G; Broomfield, H; Calonge-Contreras, M; Billet, J; Restrick, L; Stern, M
Abstract : Introduction: There is evidence that regular exercise profoundly affects both the course and outcome of COPD. While PR is well established for COPD patients limited by breathlessness, there is currently no evidence-base for follow-on LTE, which takes into account expressed desires of patients to continue exercise regularly. This pilot study aimed to evaluate an easily accessible, disease appropriate, regular LTE for COPD patients who complete PR, to confirm that it is realistic and assess whether PR benefits can be sustained. Methods: Three suitable venues, geographically distributed to maximise access, and two exercise instructors (completed Loughborough Training for Chronic Respiratory Patients) were identified. Patients completing PR were recruited into 1×weekly LTE groups. Outcomes (demographic, disease severity, functional capacity (6 min walk test (6MWT), emotional (Hospital Anxiety and Depression HAD score, CAT and Chronic Respiratory Questionnaire CRQ)) were collected at baseline, 6 and 12 months. Patient and carer satisfaction was recorded at 6 and 12 months. Attendance data were monitored throughout. Hospital admissions for 12/12 before and after LTE commenced, continues to be audited. Results: 60 COPD patients (Mean (SD) age 68.75 (10.31) yrs, FEV1 1.27 (0.56) l, 43% male, 22% current smokers, three on LTOT) were referred for LTE June 2010–May 2011. 20/60 (33%) never attended, 14/60 (23%) dropped out within 2 (1–7) months (median (range). 26/60 (43%) continue to exercise, median (range) since starting 5 (1–12) months with 50 (28)%. (Mean (SD) classes attendance. CAT, CRQ, HADS and 6MWT findings are given in the Abstract P149 table 1 . Satisfaction surveys indicate high levels of satisfaction with venue, instructor and content. No adverse events occurred during the classes. Direct cost per class (hall hire and instructor) £63. Conclusions: This pilot demonstrates feasibility of providing community-based LTE groups using instructors trained to exercise people with COPD. Patients who choose to attend LTE have moderate COPD, but high CAT scores indicating important disease impact on daily functioning. Attendance rate was high for a patient group susceptible to exacerbations, possibly reflecting high patient satisfaction. Preliminary findings suggest LTE in group settings promotes maintenance of benefits acquired from PR with further improvement in health-related quality of life (CRQ and CAT).